Insegurança hídrica domiciliar em comunidades suscetíveis a seca no município de Maranguape - CE - Lima, Antonia Adnna Guedes de (2019)
Household water insecurity is a condition shared by many families who do not have access to water in the quantity and quality necessary to meet the needs of the family unit throughout the year. This condition shows the lack of appropriate public politics for domestic water supply and emphasizes the prominent role of these families in the development of strategies for the acquisition of water and its multiple uses. The research addressed water insecurity on the household level in the city of Maranguape, Ceará, an area susceptible to drought which has districts lacking access to the services of a water supply general network. The overall aim of the research was to analyze the level of water insecurity in the households of communities susceptible to droughts through indicators related to the access to water and the socioeconomic profile of the population from interrelationships between the rainy and dry seasons, as well as, betwen rural and urban interactions. This study was developed in the districts of Jubaia and Cachoeira, located in the rural area of the city of Maranguape, Ceará, and in the municipality seat of that city, located in the urban area. In order to obtain data, a questionnaire addressing the dimensions of water insecurity was applied to 730 households during the rainy season and the dry season. The systematization and analysis of the data were done through the creation of the Household Water Insecurity Rate (in Portuguese, Índice de Insegurança hídrica Domiciliar, or IIHD) with the implementation of equations, for further comparison and validation of the data through the implementation of Cluster Analysis, Correspondence Analysis and Multivariate Analysis of Variance, which are multivariate exploration techniques. Among the main results it is possible to emphasize that water insecurity exists, though in a smaller percentage than that of water security; the households located in the municipality seat, despite having access to a water supply network, face difficulties in accessing water in proper quantity and quality; the districts of Cachoeira and Jubaia use various strategies of access and multiple uses of water, depending on the reality experienced in each period of the year; concerning the dimensions of water insecurity, the quality of water was the fact that contributed the most to the Household Water Insecurity Rate (IIHD); the period of the year and the location of the area studied have effect over water insecurity. These characteristics confirm the importance of public policies directed to domestic supply of water and that ensure the access and infrastructure necessary to the wellbeing of families, mainly during the dry season. Key-words: Water Insecurity. Domestic Supply. Water Management